If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3y + 26whenx = 2whatisy Reorder the terms: X + 26ehnwx + 3y = 2whatisy Solving X + 26ehnwx + 3y = 2ahistwy Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-26ehnwx' to each side of the equation. X + 26ehnwx + -26ehnwx + 3y = 2ahistwy + -26ehnwx Combine like terms: 26ehnwx + -26ehnwx = 0 X + 0 + 3y = 2ahistwy + -26ehnwx X + 3y = 2ahistwy + -26ehnwx Add '-3y' to each side of the equation. X + 3y + -3y = 2ahistwy + -26ehnwx + -3y Combine like terms: 3y + -3y = 0 X + 0 = 2ahistwy + -26ehnwx + -3y X = 2ahistwy + -26ehnwx + -3y Simplifying X = 2ahistwy + -26ehnwx + -3y
| logb^8=-3 | | (0.61*1.2x)+(0.39*x)=6 | | 1120=(x+3)(x+4)(5+x)(6+x)(7+x) | | (3x^y^4-11xy^4)/55xy | | 23=m-19 | | 8x+18=3x-2 | | 12(x-3)-6=2(x+5)-2(2-4x) | | 24x+12y=60 | | X/2-17=9 | | (x^4)+(8x^3)+(20x^2)+(16x)+4=0 | | -7(x-4)+5(x+2)+2(2x-1)=0 | | -7x-22= | | 10+x=16x | | 5-3x=1/3x | | 720+4x=9x | | 31=3w+9-8w | | (6x-32)/12=x/10 | | X-8=2X-10 | | 2x-1+6(2x+1)=16x-(2x-5) | | (-2/3x^3y)^3*(-2/3x^3y)^2:(-2/3x^3y)^5 | | 4x+10y=56 | | 4/9x=10 | | 20m-18=5(3m+5)+2 | | 30+2(6x-8)=2x-(5-2x+51) | | 2x^3-5x^2-10x+1=0 | | -(6x+6)+16x=33 | | x^3-5x^2-10x+5=0 | | 21=5t^2+25t | | 1/7*Ln(x) | | 14d+9=5d+45 | | 3x/5=13 | | 9n^4-10n^2+1=0 |